Fruits - essential foods - Tatiana Roșca; Maria-Gabriela Suliman (Amaltea Medical Publishing House, 2020)
What could fruits do? Reduce the inflammation in the organism, support the immune system, the hormonal system and fruits, detoxificatio, modulate the microbiome? The answer to these questions can be summarized as follows: the fruit is an essential food because the body consumes a minimal amount of energy to digest it and achieves maximum return.